2021
DOI: 10.3390/ijerph18094509
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Two Doses of Caffeine for Apnoea in Prematurity

Abstract: Caffeine is the most commonly used methyl xanthine for the prevention of apnoea in prematurity, but the ideal dose was uncertain, until now. This study compared two doses of caffeine for the prevention of apnoea in prematurity. A clinical trial was conducted on 78 preterm infants ≤32 weeks in Neonatal Intensive Care Unit. They were randomly allocated to receive the intervention (loading 40 mg/kg/day and maintenance of 20 mg/kg/day) or the control (loading 20 mg/kg/day and maintenance of 10 mg/kg/day) dose of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In this systematic review and meta-analysis of 221 trials that assessed 44 perinatal interventions, we found with moderate certainty that antenatal corticosteroids for lung maturation (small decrease) and indomethacin prophylaxis (moderate decrease) were associated with reduced risk of sIVH in preterm neonates. We also found low certainty evidence that volume-targeted ventilation (large decrease), early ESAs (moderate decrease), and prophylactic ethamsylate (moderate decrease) were associated with lower risk of sIVH, whereas UCM (moderate increase) were associated with higher risk of sIVH in preterm neonates.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this systematic review and meta-analysis of 221 trials that assessed 44 perinatal interventions, we found with moderate certainty that antenatal corticosteroids for lung maturation (small decrease) and indomethacin prophylaxis (moderate decrease) were associated with reduced risk of sIVH in preterm neonates. We also found low certainty evidence that volume-targeted ventilation (large decrease), early ESAs (moderate decrease), and prophylactic ethamsylate (moderate decrease) were associated with lower risk of sIVH, whereas UCM (moderate increase) were associated with higher risk of sIVH in preterm neonates.…”
Section: Discussionmentioning
confidence: 93%
“…We further determined the eligibility of 395 short-listed articles and excluded 174 articles for the reasons shown in eAppendix 4 in Supplement 1. A total of 221 RCTs were included in the final sample . These trials evaluated 44 interventions, which included 6 antenatal, 6 delivery room, and 32 neonatal interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it was seen that this treatment was not associated with significant adverse effects or that impact on the patient's quality of life (Du et al, 2020;Miao. et al, 2023;Kori et al, 2021).…”
Section: Side Effects and Associated Risksmentioning
confidence: 98%
“…These episodes in recent Premature births generally occur between the third and seventh day of life in babies who have respiratory distress syndrome (Elmowafi et al, 2021). It is possible to say that episodes do not controlled, prolonged and repeated apnea followed by hypoxia and bradycardia in the newborn can lead to numerous problems, such as the increased need for mechanical ventilation, difficulties in extubation and longer hospital stay (Guo et al, 2022;Kori et al, 2021).…”
Section: Introductionmentioning
confidence: 99%